Constraints Assessment Instrument Formulated The Science Learning in The Affective Domain By Primary School Teachers - Mulyani, Sri; Fitria, Yanti (International Journal of Educational Dynamics, 2019)
In this context, the teacher's Constraints in formulating Science Learning Assessment Instruments in accordance with the Affective Domain in SDN 20 Dadok Tunggul Hitam Padang. This research aims to know the constraints of teachers in Science learning assessment instrument formulated in accordance with the affective domain in SDN 20 Dadok Tunggul Hitam Padang. The approach in this study is a qualitative approach to the types of descriptive research. The subject in this study are all the teachers who teach Science Learning in SDN 20 Dadok Tunggul Hitam Padang which amounted to 18 teachers. Data collection is done using observation, and interviews. This research uses qualitative analysis of non-descriptive statistics. On the research component of the reduction of the data, and the data is done simultaneously with the process of data collection. After the data is collected, then do the reduction of data, data of the presence, and the withdrawal of the conclusion. Based on the research results obtained that the constraints experienced by teachers in formulating an assessment to determine the specifications, namely effective assessment, writing the assessment, affective domain to determine the scale of assessments, determine the scoring system, and interpreting affective domain appraisal